PENGEMBANGAN MODEL PENJADWALAN FLOWSHOP HIBRID PADA BENGKEL MRO KOMPONEN PESAWAT DENGAN PERTIMBANGAN PENUGASAN MULTI TEKNISI TETAP DAN TINGKAT KEAHLIAN TEKNISI - Furkon Hendriadi, Aditya
In general, scheduling is usually done in a manufacturing industrial production system with machines as the main processor. However, scheduling can also be applied to non-manufacturing industries, such as the service industry, with humans as the main processor. For example, scheduling can be applied in the maintenance, repair, overhaul (MRO) workshop for aircraft components. The scheduling problem at the MRO workshop is categorized as a hybrid flowshop characterized by its process flow which is divided into three stages (stripping, repairing, testing), as well as a processor that can work in parallel. This study aims to develop a hybrid flowshop scheduling model with several rules that apply in MRO workshops, namely processors in the form of homogeneous fixed multi-technicians with conditions of skill level, consideration of lead time for ordering spare parts after the stripping stage, as well as the need to use special machines at the testing stage. The scheduling model is categorized as a Mixed Integer Linear Programming (MILP) problem which produces an optimal solution, minimizing the makespan as its objective function. Model development is divided into two stages. In the first stage, changes were made to the reference model constraints, to accommodate homogeneous processing times and multi-technician rules. In the second stage, rules were added to accommodate the skill level of each technician. This model is the most comprehensive model that accommodates all predetermined rules. Scheduling model testing is carried out by executing the CPLEX program to test the model's capabilities and to find unknown model limitations.